2017
DOI: 10.1186/s12917-017-1197-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear optical microscopy of cartilage canals in the distal femur of young pigs may reveal the cause of articular osteochondrosis

Abstract: BackgroundArticular osteochondrosis is a common cause of leg weakness in pigs and is defined as a focal delay in the endochondral ossification of the epiphysis. The first demonstrated steps in the pathogenesis consist of loss of blood supply and subsequent chondronecrosis in the epiphyseal growth cartilage. Blood vessels in cartilage are located in cartilage canals and become incorporated into the secondary ossification centre during growth. It has been hypothesized that vascular failure occurs during this inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…Strands of high SHG intensity, indicating collagen fibers, appear to originate in the interior of the canal and align at the canal margin. Reproduced under the terms of the CC‐BY 4.0 license ( https://creativecommons.org/licenses/by/4.0/) . Copyright 2017, BioMed Central Ltd. f) SHG images of collagen alignment in malignant prostate biopsy, and its histological images of fused glands occupied by cancer cells.…”
Section: Bioinspired Peptide Nanostructures: Basic Linear and Nonlinementioning
confidence: 99%
See 2 more Smart Citations
“…Strands of high SHG intensity, indicating collagen fibers, appear to originate in the interior of the canal and align at the canal margin. Reproduced under the terms of the CC‐BY 4.0 license ( https://creativecommons.org/licenses/by/4.0/) . Copyright 2017, BioMed Central Ltd. f) SHG images of collagen alignment in malignant prostate biopsy, and its histological images of fused glands occupied by cancer cells.…”
Section: Bioinspired Peptide Nanostructures: Basic Linear and Nonlinementioning
confidence: 99%
“…[138,139] For example, SHG microscopy was applied as a cancer diagnostic tool [140,141] to probe the structural differences in the extracellular matrix of normal stroma, benign tumors, endometrioid tumors, and more. [142] Furthermore, SHG microscopy was used to identifying articular osteochondrosis in pigs, [143] and as an early diagnostic tool for corneal related diseases [144] and imaging of collagen distributions in human sclera. [145] SHG microscopy enabled to observe structural changes in optic nerve head structure [146] and for imaging skin damages.…”
Section: Nonlinear Optics In Biological Materials and Its Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Aseptic vascular failure has been associated with the process of incorporating vessels into the advancing ossification front [ 2 , 3 ]. Localisation may be further explained by variation in the quality of collagen type I fibres around individual vessels [ 40 42 ]. Incorporation happens a limited number of times and can therefore lead to a finite number of lesions [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies from our research group, second harmonic generation (SHG) and two photon‐excitation fluorescence (TPEF) microscopy were used to characterize normal growth cartilage and cartilage canals . These and previous studies have shown that SHG is highly sensitive and specific to collagen fibrils and that the morphology of cells could be visualized in 3D using TPEF.…”
mentioning
confidence: 99%